(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction and Aim: COVID-19 is a global pandemic caused by a virus. Vaccination prevents covid-19 infection by producing antibodies to protect from infectious diseases. After vaccination, an antibody response will appear; therefore, the development of antibodies can be measured. This study investigated Determine the antibody titers after stage 2 vaccination. Material and Methods: The type of research is descriptive with laboratory observation design to detect titers of SARS-CoV-2 antibodies. The population in this study was all the Jayapura State Health Polytechnic staff who had been vaccinated in phase 2. Samples were taken using a Random sampling technique of 35 people. Results: Over the 35 study subjects in the antibody titer measurement, 2 samples had antibody titers below the tool sensitivity value, i.e., < 20 U / ml, and 1 sample had an antibody titer above the tool sensitivity value of > 12,500 U / ml with a mean value of 2533. The percentage of employees who are positive to achieve antibodies at the Jayapura State Health polytechnic after phase 2 vaccination is 94.3%. Conclusion: An increase in the level of Covid-19 antibodies was found in employees and staff of the Jayapura Ministry of Health Health Polytechnic after stage 2 vaccination